Delayed Administration of Nintedanib Ameliorates Fibrosis Progression in CG-Induced Peritoneal Fibrosis Mouse Model - Binbin Cui; Chao Yu; Shenglei Zhang; Xiying Hou; Yi Wang; Jun Wang; Shougang Zhuang; Feng Liu (Karger Publishers, 2022)
Background: A multiple-target tyrosine kinase inhibitor, nintedanib, which is approved for treatment of interstitial pulmonary disease, has been demonstrated to have anti-fibrotic activity outside of the lungs. We explored its therapeutic effect in a murine model of peritoneal fibrosis. Methods: Daily intraperitoneal injections of chlorhexidine gluconate (CG) induced peritoneal fibrosis in mice. The effects of delayed administration of nintedanib (given at day 21 after CG injection and then given daily for 14 days) were determined by immunohistochemical staining, ELISA, and immunoblot analysis. Results: Delayed administration of nintedanib significantly inhibited peritoneal fibrosis progression as indicated by decreasing deposition and expression of extracellular matrix (ECM) proteins (fibronectin and type I collagen). Treatment with nintedanib also upregulated MMP-2 and reciprocally downregulated TIMP-2, along with reducing expression of α-SMA, β-vimentin, and two transcription factors (Snail and Twist), and retaining E-cadherin expression. Nintedanib also inhibited co-expression of β-vimentin with Snail or Twist as shown by immunofluorescent staining. Moreover, nintedanib decreased the number of CD31-positive blood vessels and CD31 expression in the injured peritoneum. Moreover, delayed application of nintedanib inhibited the expression of several cytokines/chemokines, including monocyte chemoattractant protein-1, tumor necrosis factor-α, interleukin-1β (IL-1β), and IL-6, and infiltration of CD68+ macrophages to the injured peritoneum. Finally, nintedanib blocked phosphorylation of STAT3, NF-κB, and Smad3 during the development of peritoneal fibrosis. Conclusions: Delayed administration of nintedanib inhibits progression of peritoneal fibrosis and partially reverses established peritoneal fibrosis by attenuating epithelial-mesenchymal transition, inflammation, and angiogenesis, as well as promoting ECM degradation. We conclude that nintedanib has a therapeutic potential to treat peritoneal fibrosis.